Efectos de un programa de intervención en vocabulario, conciencia morfológica y fonológica en niños de jardín de infantes en lectura en grado 1 : Effects of an intervention program on vocabulary, morphological and phonological awareness in kindergarden children on grade 1 reading achievement - Maria Elsa Porta, Gloria Ramirez (Revista de Orientación Educacional, 2020)
Este estudio evalúa el impacto de dos tipos de intervención (conciencia fonológica (CF) versus una intervención combinada en CF, vocabulario y conciencia morfológica CM)) comparadas con la enseñanza regular sobre el nivel lector adquirido al final de primer grado en niños de Jardín de Infantes (N = 129) de bajo nivel socioeconómico. Obtuvimos mediciones preliminares y posteriores a la intervención de CF, CM, vocabulario, lectura y comprensión lectora. Los niños que recibieron la intervención combinada tuvieron un desempeño superior a los niños del grupo control y a los que recibieron intervención únicamente en CF en las pruebas de vocabulario y comprensión lectora. También superaron al grupo control en CM y lectura. La intervención más efectiva fue la que incluyó tres componentes críticos de la lectura: CF, conciencia morfológica, y vocabulario. Estos hallazgos tienen implicaciones teóricas para un modelo más integral del desarrollo de la lectura en español y prácticas para la efectiva evaluación e intervención temprana en la lectura. Abstract The purpose of this study was to investigate the impact of two interventions (phonological awareness (PA) only versus a combined intervention on PA, vocabulary, and morphological awareness (MA)) in Argentinean kindergarteners from low SES on their reading comprehension at the end of grade one. Participants were 129 Spanish monolingual, Argentinian children from low SES backgrounds. Using a pre-posttest quasi-experimental design, we compared three conditions: (a) intervention on PA only, (b) combined intervention (PA + vocabulary + MA), (c) control group (business as usual). Kindergarten teachers implemented the interventions with support (for small group intensive work) by speech and language pathologists, over a period of three months (22 hours total). Participating children were assessed on vocabulary, letter-word identification, PA, and MA in kindergarten (before and after the intervention) and in grade one, and on reading comprehension in grade one only. Repeated ANOVAS indicated that children receiving the combined intervention outperformed children in the PA only intervention on vocabulary and reading comprehension and the control group in MA and reading. Findings suggest that the combined intervention was the most effective. These findings have theoretical implications for a more comprehensive developmental model of reading in Spanish, as well as practical implications for teaching and assessment of literacy skills in young, monolingual Spanish-speaking children from low-socioeconomic backgrounds.